Health effects of instruction intensity: Evidence from a natural experiment in German high-schools - Johanna Sophie Quis; Simon Reif (Bamberg University, Bamberg Economic Research Group (BERG), 2017)
A large literature aims to establish a causal link between education and health using changes in compulsory schooling laws. It is however unclear how well more education is operationalized by marginal increases in school years. We shed a new light on this discussion by analyzing the health effects of a reform in Germany where total years of schooling for students in the academic track were reduced from nine to eight while keeping cumulative teaching hours constant by increasing instruction intensity. The sequential introduction of the reform allows us to implement a triple difference-in-differences estimation strategy with data from the German Socio-Economic Panel. We find that increased weekly instruction time has negative health effects for females while they are still in school. However, after graduation, females even seem to benefit from reduced school years. We find no effects on males' health.
Keywords: I19; I21; I28; 330; education and health; instruction intensity; natural experiment; SOEP